Use of a falls incident reporting system to improve care process documentation in nursing homes. Issue 2 (2nd April 2008) - Wagner, L M; Capezuti, E; Clark, P C; Parmelee, P A; Ouslander, J G
Abstract : Background: Falls are the most frequently reported adverse event among frail nursing home residents and are an important resident safety issue. Incident reporting systems have been successfully used to improve quality and safety in healthcare. The purpose of this study was to test the effect of a systematically guided menu-driven incident reporting system (MDIRS) on documentation of post-fall evaluation processes in nursing homes. Methods: Six for-profit nursing homes in southeastern USA participated in the study. Over a 4-month period, MDIRS was used in three nursing homes matched with another three nursing homes which continued using their existing narrative incident report to document falls. Trained geriatric nurse practitioner auditors used a data collection audit tool to collect medical record documentation of the processes of care for residents who fell. Multivariate analysis of covariance was used to compare the post-fall nursing care processes documented in the medical records. Results: 207 medical records of resident who fell were examined. Over 75% of the sample triggered at high risk for falls by the minimum data set. An adequate neurological assessment was documented for only 18.4% of residents who had experienced a fall. Although two-thirds of the sample had a diagnosis of incontinence, less than 20% of the records had incontinence-related interventions in the nursing care plan. Overall, there was more complete documentation of the post-fall evaluation process in the medical records in nursing homes using the MDIRS than in nursing homes using standard narrative incident reports (p<0.001). Conclusion: Further improvements are necessary in reporting mechanisms to improve the post-fall assessment in nursing home residents.